Impacts of building layout on pedestrian level wind comfort and gas pollutant diffusion - Yi Yang; Tianxiao Zhang; Haiying Xie; Xiaoxiao Wang (Journal of Air Pollution and Health, 2021)
Introduction: The impacts of building layout on pedestrian level wind comfort and gas pollutant diffusion are simulated using computational fluid dynamics method. Materials and methods: The control equations of flow and pollutant diffusion are solved by using ANSYS Fluent. The SIMPLE algorithm is selected for the pressure-velocity coupling. The data from wind tunnel experiment at Tokyo Polytechnic University is employed in the validation case. Results: The velocity field and turbulence intensity at pedestrian level under different building layouts are obtained. The distribution and evaluation of wind comfort grade and pollutant concentration are given. Conclusion: Building layouts have significant impacts on flow and pollutant diffusion at pedestrian level. The outward staggered layout of building group can improve both wind comfort grade and air quality, but the inward staggered layout has the adverse effect. Non-staggered layouts are the worst in terms of the wind comfort grade in this paper.